Development of the Life Insurance Market in Albania - Madani, Assoc. Prof.Dr Filloreta; Bazini, Evelina (European Journal of Economics and Business Studies, 2017)
Life insurances occupy a small part in the insurance market in developing countries. The new age of the insurance industry and the level of the economic development in Albania make the life insurance market even more fragile. Factors affecting the development of this market are influenced by the economic growth and by other factors such as inflation, education of population, population growth, government policies, private investment, etc. In this article we will analyze using statistical methods the degree of the impact of the above factors in the life insurance market and we will also analyze through penetration coefficients the impact of the life insurance industry in Albania's economic development.
Keywords: Life insurance, age, income per capita, level of education, Non-life insurance